Molecular events in the clinicopathological diagnosis of alveolar osteitis - Talaya Zahid; Sarah Ghafoor (Journal of the Pakistan Medical Association, 2020)
Abstract Alveolar osteitis (AO) is an extremely distressing outcome following extraction of tooth. Its pathophysiology is poorly understood due to varied nature of presentation of the condition. However, a delay in the healing process of bone due to fibrinolysis is believed to be the underlying pathophysiology. This review highlights three major risk factors – trauma, bacterial accumulation due to poor oral hygiene, and smoking – in causing alveolar osteitis, and describes underlying related molecular events. Fibrinolysis results due to traumatic tooth extraction as well as due to accumulation of certain microorganisms which leads to the development of alveolar osteitis. Tumour necrosis factor-alpha (TNF-?), Runt-related transcription factor 2 (Runx 2) and osteocalcin (OCN) can be used as molecular markers for evaluating alveolar osteitis. Assessment assays of such biomarkers can lead to a better understanding of the pathological process in providing a clearer picture to researchers and clinicians. Continuous...